The Effect of Experiential Learning Model in Elementary School - Nurul Fatmanisa; La Ode Amril; Ratna Wahyu Wulandari (Universitas Djuanda, 2020)
This study aims to understand the impact of learning models experiential learning on students' mathematical problem solving abilities. This research was conducted at SDN Banjarwaru 01, Ciawi District, Bogor Regency in 2017/2018. The study used the Posttest Only Control Group Design. The subjects involved in the study were 54 students in class V SDN Banjarwaru 01. Data collection is obtained through interviews, observations and tests. Analysis of the data used is descriptive analysis and inferential statistical analysis. The final results of the study used the t-test in the ability to solve students' mathematical problems by obtaining a significance of 0.000 <0.05. From the t-test results listed can be obtained that the application of experiential learning learning models in mathematics has an effect on the development of problem-solving abilities of students of SDN 01 Banjarwaru Bogor district.